Fatty Acid Amide Hydrolase Inhibition by JNJ‐42165279: A Multiple‐Ascending Dose and a Positron Emission Tomography Study in Healthy Volunteers. Issue 4 (25th March 2018) - Postnov, Andrey; Schmidt, Mark E.; Pemberton, Darrel J.; de Hoon, Jan; van Hecken, Anne; van den Boer, Maarten; Zannikos, Peter; van der Ark, Peter; Palmer, James A.; Rassnick, Stef; Celen, Sofie; Bormans, Guy; et al.
Abstract: Inhibition of fatty acid amide hydrolase (FAAH) potentiates endocannabinoid activity and is hypothesized to have therapeutic potential for mood and anxiety disorders and pain. The clinical profile of JNJ‐42165279, an oral selective FAAH inhibitor, was assessed by investigating the pharmacokinetics, pharmacodynamics, safety, and binding to FAAH in the brain of healthy human volunteers. Concentrations of JNJ‐42165279 (plasma, cerebrospinal fluid (CSF), urine) and fatty acid amides (FAA; plasma, CSF), and FAAH activity in leukocytes was determined in a phase I multiple ascending dose study. A positron emission tomography study with the FAAH tracer [ 11 C]MK3168 was conducted to determine brain FAAH occupancy after single and multiple doses of JNJ‐42165279. JNJ‐42165279 administration resulted in an increase in plasma and CSF FAA. Significant blocking of brain FAAH binding of [ 11 C]MK3168 was observed after pretreatment with JNJ‐42165279. JNJ‐42165279 produces potent central and peripheral FAAH inhibition. Saturation of brain FAAH occupancy occurred with doses ≥10 mg of JNJ‐42165279. No safety concerns were identified.